On the RESTful Web Services for Managing Application Virtualization Environments - Yildiz, Elif Cansu; Unal, Engin; Tuzun, Hakan; Aktas, Doruk Eren; Aktas, Mehmet S. (IEEE, 2019)
Today, application virtualization environments are used in many different fields. With the spread of application virtualization environments, solutions to manage these environments have become an important necessity today. Within the scope of this research, we propose a design of a RESTful web service for managing application virtualization environments. In this manuscript, we discuss the programming interface of the proposed service in detail. We describe our approach when designing semantics for the RESTful web service. We overview application usage scenarios in which our design has successfully been used. To show the usability of the proposed design, a prototype implementation is developed. The performance of the prototype implementation for different functionalities is evaluated. The evaluation results indicate that the proposed service can be utilized in the management of application virtualization environments.
Keywords: application virtualization environments; RESTful web service; container management systems; scalibility; management of containers; Computer Science